The Ever-emerging markets : why economic forecasts fail - Sharma, Ruchir (2014)
Argues that although single-factor theories are appealing, they ignore the rapid shifts of global competition and so provide no persuasive scenario on which to base planning for the next five to ten years. Calls instead for the forecaster to track a shifting list of a dozen factors, from politics to credit and investment flows, to assess the growth prospects of each emerging nation. Notes that it aims to produce a practical guide for following the rise and fall of nations in real time and in the foreseeable future.